BioCarbon Fund Experience : Insights from Afforestation and Reforestation Clean Development Mechanism Projects - World Bank (Washington, DC, 2017)
Carbon finance recognizes the contribution of projects to mitigating climate change. To be able to access carbon finance, projects can certify their emission reductions under a variety of standards, one of which is the Clean Development Mechanism (CDM) of the United Nations Framework Convention on Climate Change (UNFCCC). Project developers can sell their carbon credits either in the voluntary or the regulated market. Since 2002, projects from diverse sectors have been applying the CDM modalities and procedures to generate Certified Emission Reductions (CERs) that are traded in the carbon market Afforestation/Reforestation (A/R) is one out of the 15 sectors that can generate carbon credits under the CDM. The purpose of this document is to share the experience of the BioCarbon Fund (BioCF) of the World Bank in developing and implementing 21 A/R CDM projects in 16 countries. This experience shows that the benefits associated with A/R CDM projects support the livelihood of rural people and their local environment in a significant manner. However, depending on their capacity, projects may struggle with getting credit certification and the associated benefits. This report presents the opportunities and challenges A/R CDM projects face and presents recommendations to facilitate their design and implementation as well as to scale them up significantly.